Actuation of Three‐Dimensional‐Printed Nanocolloidal Hydrogel with Structural Anisotropy. (22nd February 2021) - Gevorkian, Albert; Morozova, Sofia M.; Kheiri, Sina; Khuu, Nancy; Chen, Heyu; Young, Edmond; Yan, Ning; Kumacheva, Eugenia
Abstract: Polymer hydrogels exhibit actuation properties that result in reversible shape transformations and have promising applications in soft robotics, drug delivery systems, sensors, and microfluidic devices. Actuation occurs due to differential hydrogel swelling and is generally achieved by modulating hydrogel composition. Here a different approach to hydrogel actuation that originates solely from its structural anisotropy is reported. For 3D‐printed single‐layer hydrogels formed by cellulose nanocrystals (CNCs) and gelatin methacryloyl it is shown that shear‐induced orientation of CNCs results in anisotropic mechanical and swelling properties of the hydrogel. Upon swelling in water, planar hydrogels acquire multiple complex 3D shapes that are achieved by i) varying CNC orientation with respect to the shape on the hydrogel sheet and ii) patterning the hydrogel with the regions of shear‐mediated and random CNC orientation. This study shows the capability to generate multiple shapes from the same hydrogel actuator based on the degree of its structural anisotropy. In addition, it introduces a biocompatible nanocolloidal ink with shear‐thinning and self‐healing properties for additive manufacturing of hydrogel actuators. Abstract : A single‐layer 3D‐printed nanocolloidal hydrogel actuator undergoes shape morphing solely due to structural anisotropy. Programmable shape transformations are triggered by changing the orientation of nanoparticles with respect to the long axis of the hydrogel sheet and by patterning the sheet with actuating and non‐actuating regions.